1987
DOI: 10.1002/bit.260300316
|View full text |Cite
|
Sign up to set email alerts
|

Enzyme‐Entrapping behaviors in alginate fibers and their papers

Abstract: Enzyme immobilization in the form of fiber and paper was easily achieved by wet spinning of aqueous admixture of sodium alginate and enzymes into divalent metallic ion solution as a coagulating bath, followed by paper making of resultant shortly cut fibers. Entrapment yields of enzymes used, e.g., glucoamylase, cyclodextrin glucanotransferase, endo-polygalacturonase, and protease, were always higher in calcium alginate fibers and their papers than those in corresponding beads. It was found that the yields incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

1990
1990
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 20 publications
(1 reference statement)
0
6
0
Order By: Relevance
“…Kobayashi et al 45 used alginate fibers for enzyme immobilization. They spun an aqueous mixture of sodium alginate and enzymes into divalent metallic ion solution as a coagulating bath to produce enzyme‐containing fibers.…”
Section: Production Of Other Novel Alginate Fibersmentioning
confidence: 99%
“…Kobayashi et al 45 used alginate fibers for enzyme immobilization. They spun an aqueous mixture of sodium alginate and enzymes into divalent metallic ion solution as a coagulating bath to produce enzyme‐containing fibers.…”
Section: Production Of Other Novel Alginate Fibersmentioning
confidence: 99%
“…Schmid 1989) or the multiple use of the enzyme by its immobilization may be done. Several authors (Kobayashi et al 1987; Crump and Rozzell 1988;Yang and Su 1989) have already demonstrated the successful entrapment or covalent coupling of Bacillus macerans CGTase and its suitability for continuous CD production.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, either a mild fiber fabrication procedure or a robust enzyme is required, which restricts the selection of raw materials. Chemical functional groups on the supports are not essential for immobilization, but they can either be used to facilitate the immobilization procedure through enzyme–matrix interactions, or to adjust the porosity of the fibrous membrane [ 8 , 67 , 136 , 214 ].…”
Section: Fibrous Membrane Immobilization Supportsmentioning
confidence: 99%
“…Diverse forms of silica or silica-based particles synthesized by the sol-gel method [ 8 , 127 , 160 ] or water-soluble polymers [ 29 , 67 , 136 , 137 , 162 , 171 , 214 ] are commonly used as enzyme incorporation matrices. These polymers have the potential for being processed into fibrous membranes [ 98 , 172 , 173 , 187 ].…”
Section: Fibrous Membrane Immobilization Supportsmentioning
confidence: 99%